Atrial mitral regurgitation: Characteristics and outcomes of transcatheter mitral valve edge‐to‐edge repair. Issue 1 (10th May 2022) - Simard, Trevor; Reddy, Yogesh N. V.; Thaden, Jeremy J.; Padang, Ratnasari; Michelena, Hector I.; Nkomo, Vuyisile T.; Lloyd, James W.; El Sabbagh, Abdallah; Nishimura, Rick A.; Reeder, Guy S.; Guerrero, Mayra; Alkhouli, Mohamad; et al.
Abstract: Background: Mitral transcatheter edge‐to‐edge repair (MTEER) is an established therapeutic approach for mitral regurgitation (MR). Functional mitral regurgitation originating from atrial myopathy (A‐FMR) has been described. Objectives: We sought to assess the clinical, echocardiographic and hemodynamic considerations in A‐FMR patients undergoing MTEER. Methods: From 2014 to 2020, patients undergoing MTEER for degenerative MR (DMR), functional MR (FMR), and mixed MR were assessed. A‐FMR was defined by the presence of MR > moderate in severity; left ventricular (LV) ejection fraction (LVEF) ≥ 50%; and severe left atrial (LA) enlargement in the absence of LV dysfunction, leaflet pathology, or LV tethering. The diagnosis of A‐FMR (vs. ventricular‐FMR [V‐FMR]) was confirmed by three independent echocardiographers. Baseline characteristics, procedural outcomes as well as clinical and echocardiographic follow‐up are reported. Device success was defined as final MR grade ≤ moderate; MR reduction ≥1 grade; and final transmitral gradient <5 mmHg. Results: 306 patients underwent MTEER, including DMR (62%), FMR (19%), and mixed MR (19%). FMR cases included 37 (63.8%) V‐FMR and 21 (36.2%) A‐FMR. Tricuspid regurgitation (≥ moderate) was higher in A‐FMR (80.1%) compared to V‐FMR (54%) and DMR (42%). Device success did not significantly differ between A‐FMR and V‐FMR (57% vs. 73%, p = 0.34) or DMR (57% vs. 64%, p = 1.0). The A‐FMR cohort was less likely to achieve ≥3 grades of MR reduction compared to V‐FMR (19% vs. 54%, p = 0.01) and DMR (19% vs. 49.7%, p = 0.01). Patients with V‐FMR and DMR demonstrated significant reductions in mean left atrial pressure (LAP) and peak LA V‐wave, though A‐FMR did not (LAP −0.24 ± 4.9, p = 0.83; peak V‐wave −1.76 ± 9.1, p = 0.39). In follow‐up, echocardiographic and clinical outcomes were similar. Conclusions: In patients undergoing MTEER, A‐FMR represents one‐third of FMR cases. A‐FMR demonstrates similar procedural success but blunted acute hemodynamic responses compared with DMR and V‐FMR following MTEER. Dedicated studies specifically considering A‐FMR are needed to discern the optimal therapeutic approaches.